2016
DOI: 10.1093/fampra/cmw051
|View full text |Cite
|
Sign up to set email alerts
|

Association between unexplained hypoalbuminaemia and new cancer diagnoses in UK primary care patients

Abstract: Low albumin levels were associated with an increased risk of cancer. This finding needs to be confirmed in other primary care populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Although simple blood tests are often used to investigate non-specific symptoms in primary care patients,131415 the role of such tests in selecting those with unexpected WL for further cancer investigation is poorly understood. Abnormal test results might facilitate patient triage,1617 be poor predictors of cancer,1819 or be predictive across several cancer sites 20. Triage testing in primary care is important to avoid unnecessary urgent referrals of patients for invasive investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Although simple blood tests are often used to investigate non-specific symptoms in primary care patients,131415 the role of such tests in selecting those with unexpected WL for further cancer investigation is poorly understood. Abnormal test results might facilitate patient triage,1617 be poor predictors of cancer,1819 or be predictive across several cancer sites 20. Triage testing in primary care is important to avoid unnecessary urgent referrals of patients for invasive investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Merriel et al , in a 12-month follow-up of a total of 5753 patients with serum albumin less than 3.5 g/dL, 28.4% patients eventually developed cancer. The authors concluded that patients with low albumin had OR of 2.29 of having diagnosed with a cancer in following 12 months 6…”
Section: Discussionmentioning
confidence: 99%
“…The strength of this study was the long follow-up and the large number of subjects. Moreover, the data from the Swedish National Cause of Death Register are comprehensive, comprising almost all the inhabitants (99%) that have died and their cause of death [22]. A study showed 77% agreement between the registered cause of death and the results from a medical record investigation, with the agreement being higher in the younger age quartiles for malignant neoplasms [23].…”
Section: Strength and Weaknesses Of The Studymentioning
confidence: 99%